Uncovering Theological Inconsistencies in the History of Agathangelos - Sahakyan, Fr. Movses (Davit) (Mesrop Mashtots Institute of Ancient Manuscripts)
This paper analyses the theological inconsistencies in two prayer-texts from the 5th-century History [of Armenia] by Agathangelos (Agat‘angeghay Patmut‘iwn [Hayotsʻ]). Were these inconsistencies manifest in the original composition or arose during later editing and transcription? Through an examination of all the editions of the work, the author argues that the controversial passages in the two prayer-texts may not be original, despite their longstanding presence. They create tension and challenge the coherence between theological tenets within the prayers and throughout the History.
Keywords: Philology